Demand for religion and its impact on economic growth - A. Somasundram, Sotheeswari (2018)
Religion has in recent years taken center stage in the landscapes of many countries influencing outcomes either directly or indirectly. The interconnectedness of religion to the different facets of human life inevitably influences nations and their performance. In setting the context for this research, this study alluded to Adam Smith’s theory of the capital value of reputation which states that a religious person is perceived as having high moral values and this positive reputation leads to favorable gains when participating in market exchanges. The inquiry of the present study is, if the theory of the capital value of reputation is applied at the country level, would lack of demand for religion lead to countries been perceived as less reputable and would this have a negative impact on economic performance. In order to gain a comprehensive understanding on this area, the study initially focused on examining the determinants of demand for religion both at a micro as well as a macro level, and subsequently investigated the impact of demand on economic performance of nations based on four theoretical pillars, Theory of Capital Value of Reputation, Azzi Ehrenberg Theory, Secularization Theory and Religious Economies Theory. The study used three techniques to achieve its objectives. For the first objective, the study applied Structural Equation Modelling (SEM) to estimate 1208 respondents’ demand for religion using data from ISSP Research Group. The second objective utilized the Quantile Regression to estimate the aggregate demand for religion involving 83 countries for 2010. The last objective applied the Generalized Method of Moments (GMM) estimators to estimate the heterogeneous panel model for 59 countries for the period 1981 – 2014. Findings revealed that demand for religion at the individual level were influenced by price, income, religious upbringing, and complementary product while moderated by gender and shared faith marriages. The drivers of demand for religion at a macro level were income, religious regulations, religious diversity and state religion in Christian majority nations. However, these determinants were only applicable for countries recording a lower demand for religion. The findings also revealed that religiosity influences growth negatively, where religious participation diverted resources away from productive use, contributing towards a decline in economic performance. In proposing policy recommendations, the suggestions were geared towards the key roles that religious organizations and the policy makers can play in increasing participation while ensuring the religious market contributes positively towards the growth of a nation.